The impact of sustainable urban planning on land property and markets in Sharjah - ALYAFEI, ABDELRAHMAN OMAR ABDUALLAH (2019)
Modern civilization faces numerous challenges in its quest to meet its needs despite the limited nature of the available natural resources available to humanity. The nature of land as a natural resource supports the arguments opining for the implementation of sustainable urban planning (SUP) measures. The implementation of sustainable urban planning measures in Sharjah must target essential aspects such as housing, infrastructure, and social amenities among other notable and desirable outcomes. The information collected from the survey indicates that land is one of the most valuable resources in Sharjah despite it’s less than optimal use within Sharjah. Furthermore, Sharjah can attract growth by developing its infrastructure, improving its social amenities, incentivizing economic growth and improving its healthcare sector. Such measures are only possible if supported by the local authority in tandems with the relevant stakeholders to implement even development across the underdeveloped and developed urban areas. Finally, the implementation of SUP should focus on introducing economic-development oriented activities to boost its appeal in collaboration with the government as the supervisory body on all proceedings. The findings further suggest several policies that could improve Sharjah’s standing that include incentivized trade policy, property rights and SME funding policy, natural resource protection policies, green building and construction policies, ethics regulation in the industrial sector policy, and finally the land use and land price regulation policy. Further consultation with experts and local authority affirms that the introduction of these policies will have the desired effect on Sharjah with an emphasis placed on land use regulation. In that regard, the study findings documented in this report are essential to the future of Sharjah particularly in improving its lands market standing